2013
DOI: 10.1002/hyp.10050
|View full text |Cite
|
Sign up to set email alerts
|

Stemflow on the woody parts of plants: dependence on rainfall intensity and event profile from laboratory simulations

Abstract: This paper presents the first experimental study of how rainfall intensity and event profile affects stemflow behaviour on the rigid branches and stems of leafless, woody plants. Constant intensity rainfall simulation experiments showed that stemflow fraction rises with intensity. Varying intensity experiments showed that the stemflow fraction and stemflow flux vary with the rainfall event intensity profile and peak intensity. Stemflow fraction tends to be larger when intensity peaks occur early in the rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
1
35
0
1
Order By: Relevance
“…Dunkerley [] conducted a laboratory experiment to investigate stemflow production on the woody parts of trees (branches and boles) in relation to rainfall intensity and event profile. He observed that simulated events of variable intensity produced larger peak stemflow fluxes than events with rainfall of constant intensity; moreover, stemflow fractions of P were larger if peak rainfall intensities were greater in the earlier portion of an event.…”
Section: Stemflow Dynamics As a Function Of Temporal Scale And Meteormentioning
confidence: 99%
“…Dunkerley [] conducted a laboratory experiment to investigate stemflow production on the woody parts of trees (branches and boles) in relation to rainfall intensity and event profile. He observed that simulated events of variable intensity produced larger peak stemflow fluxes than events with rainfall of constant intensity; moreover, stemflow fractions of P were larger if peak rainfall intensities were greater in the earlier portion of an event.…”
Section: Stemflow Dynamics As a Function Of Temporal Scale And Meteormentioning
confidence: 99%
“…Nutrient levels under scattered trees are typically enhanced by litter accumulation (Barnes et al, 2011) and decomposition from microbial activity (Fterich et al, 2012), nutrient inputs from animal dung (Dean et al, 1999;Allington and Valone, 2014), mining of nutrients by tree roots (Belsky, 1994;Wilson et al, 2007) and the interception of nutrients by trees from aeolian processes (Li et al, 2008), and from hydrologic processes such as surface runoff (Parsons et al, 1992;Schlesinger et al, 1999) and rainfall through stemflow (Whitford et al, 1997;Dunkerley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Diameter at breast height ( DBH ) is usually a strong predictor of SF production (Deguchi et al ., ; André et al ., ; Šraj et al ., ; Germer et al ., ; Van Stan and Levia, ), but studies showing high yields for small trees (Germer et al ., ; Levia et al ., ) are stimulating further research. Wood cover fraction and wood volume have implications for SF , particularly during seasonal defoliation when increased SF in leaf‐off condition has often been observed (André et al ., ; Dunkerley, ). In a study of 10 European beech saplings, Levia et al .…”
Section: Introductionmentioning
confidence: 99%